International Journal of Ambient Energy - International Journal of Ambient Energy (Taylor & Francis, 2026)
Informing energy policy, innovation and application through a critical analysis of deployment potential, the International Journal of Ambient Energy publishes high quality innovative energy research that demonstrates the potential for carbon reductions in real-world applications. The Journal reports original research, review papers, book reviews, applications and case-studies on all areas of this subject, including nuclear, hydroelectric, wind, biomass, solar, photovoltaic, tidal, wave and geothermal power. A critical analysis of theoretical and practical research facilitates a greater understanding of its potential use in alternative applications, use in different regions and ultimately greater acceptance in practice.
FI 0.31
Q3
Keywords: Engineering; Computing & Technology; Energía ambiental; Acuerdos transformativos; Transformative agreements; Energía nuclear; Geotermia